High-weather-resistant anticorrosive epoxy resin coating and preparation method thereof

By synthesizing modified epoxy resin and modified polysulfide rubber, functional groups such as diazole fluorene structure, glass flakes, POSS and hydroxyl groups were introduced, which solved the problems of insufficient weather resistance and poor corrosion resistance of epoxy resin coatings in high temperature and high humidity environments, and achieved excellent coating performance.

CN119859455AActive Publication Date: 2025-04-22WUXI XINERQI CHEM TECH CO LTD

Patent Information

Application Number
CN202510162223.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-22
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

Epoxy resin coatings have problems such as insufficient weather resistance, poor corrosion resistance and prone to cracking in high temperature and high humidity environments, which are difficult to meet the needs of long-term anti-corrosion coatings.

Method used

By synthesizing modified epoxy resins and modified polysulfide rubber, the introduction of diazole structures and glass flakes will enhance the corrosion resistance and mechanical properties of the paint, and by introducing functional groups such as POSS and hydroxyl groups, the heat resistance of the paint and weather resistance in high temperature and high humidity environments will be improved.

Benefits of technology

It significantly improves the corrosion resistance, mechanical strength and weather resistance of epoxy resin coatings in high temperature and high humidity environments, and meets the demand for epoxy resin coatings with excellent performance.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a high-weather-resistant anticorrosive epoxy resin coating and a preparation method thereof, and relates to the field of coatings. The high-weather-resistance anticorrosive epoxy resin coating is prepared from the following raw materials in parts by weight: 50 to 55 parts of modified epoxy resin, 30 to 35 parts of amino resin, 15 to 17 parts of urea resin, 10 to 12 parts of modified polysulfide rubber, 8 to 10 parts of titanium dioxide, 3 to 5 parts of kaolin, 0.5 to 1.0 part of dispersing agent, 0.6 to 0.8 part of flatting agent, 0.2 to 0.4 part of defoaming agent, 0.8 to 1.0 part of drier and 15 to 20 parts of solvent. The modified epoxy resin is obtained by introducing a diazafluorene structure and glass flakes into an epoxy resin molecular chain; the modified polysulfide rubber is obtained by introducing POSS (Polyhedral Oligomeric Silsesquioxane), hydroxyl and an alkane long chain into a polysulfide rubber molecular chain. The epoxy resin coating disclosed by the invention has excellent corrosion resistance, mechanical strength and weather resistance in high-temperature and high-humidity environments, and is worthy of popularization and application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of coatings, and in particular to a highly weather-resistant and anti-corrosion epoxy resin coating and a preparation method thereof. Background Art

[0002] Epoxy resin is widely used in coatings, adhesives, composite materials and other fields due to its small shrinkage during the curing reaction, and the adhesion, heat resistance, chemical resistance, mechanical properties and electrical properties of the cured product. However, due to its molecular structure, epoxy resin cured products have large internal stress, brittleness, poor impact resistance and easy cracking. In order to improve these shortcomings, epoxy resin needs to be toughened. Since the main chain structure of polysulfide rubber molecules is connected by single bonds and contains a large number of ether bonds, the molecular chain is extremely flexible and has high compatibility with epoxy resin. It is often used to toughen epoxy resin. However, the heat resistance of polysulfide rubber does not meet the use requirements of epoxy resin coatings with higher heat resistance requirements.

[0003] Moreover, the development of epoxy resin in the field of long-term anti-corrosion coatings is limited due to its poor water resistance, low toughness, and reduced adhesion after long-term use. The anti-corrosion performance of epoxy resin coatings does not meet the current use requirements. In addition, affected by factors such as high temperature, humidity, and rain, epoxy resin coatings will age to varying degrees, resulting in reduced lifespan, increased use costs, and waste of resources. Therefore, the weather resistance of epoxy resin coatings needs to be improved urgently.

[0004] In summary, a suitable modification method is needed to apply polysulfide rubber with improved heat resistance to epoxy resin coatings, while improving the corrosion resistance and water resistance of epoxy resin coatings, so as to obtain epoxy resin coatings with excellent properties such as corrosion resistance and weather resistance in high temperature and high humidity environments. Summary of the invention

[0005] In order to solve the above technical problems, the present invention provides a highly weather-resistant and anti-corrosion epoxy resin coating and a preparation method thereof.

[0006] The purpose of the present invention can be achieved through the following technical solutions: A highly weather-resistant and anticorrosive epoxy resin coating, comprising the following raw materials in parts by weight: 50-55 parts of modified epoxy resin, 30-35 parts of amino resin, 15-17 parts of urea-formaldehyde resin, 10-12 parts of modified polysulfide rubber, 8-10 parts of titanium dioxide, 3-5 parts of kaolin, 0.5-1.0 parts of dispersant, 0.6-0.8 parts of leveling agent, 0.2-0.4 parts of defoamer, 0.8-1.0 parts of drying agent and 15-20 parts of solvent; Furthermore, the dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is potassium isooctanoate, and the solvent is ethyl acetate; The highly weather-resistant and anti-corrosion epoxy resin coating is prepared by the following steps: after the modified epoxy resin, urea-formaldehyde resin and modified polysulfide rubber are stirred and mixed at 80-90° C. for 2-2.5 hours, the amino resin is added and stirred at 60-70° C. for 1-1.5 hours, titanium dioxide, kaolin, dispersant, leveling agent, defoamer, drying agent and solvent are added and stirred at 60-70° C. for 1.5-2.0 hours, so as to obtain the highly weather-resistant and anti-corrosion epoxy resin coating; The modified epoxy resin is prepared by the following steps: Step A1, adding 1,10-phenanthroline-2-carboxylic acid methyl ester and potassium hydroxide to deionized water and stirring at 75-80° C. for 20-30 min, then adding potassium permanganate aqueous solution dropwise thereto, and completing the addition within 4.5-5 h, continuing to stir the reaction for 3-3.5 h, hot filtering, concentrating, recrystallizing in water, and vacuum drying at 70-80° C. overnight to obtain reaction product 1; Furthermore, the dosage ratio of 1,10-phenanthroline-2-carboxylic acid methyl ester, potassium hydroxide, deionized water, and potassium permanganate aqueous solution is 3.8-4.0 g: 2.6-2.8 g: 170-175 mL: 111-115 mL; the potassium permanganate aqueous solution is obtained by adding 6.5-6.7 g of potassium permanganate to 105-110 mL of deionized water and stirring and mixing; During the reaction of step A1, 1,10-phenanthroline-2-carboxylic acid methyl ester is oxidized by potassium permanganate to obtain a reaction product 1 containing an ester group and fluorenone; Step A2, adding the dried glass flakes to an ethanol aqueous solution and stirring for 15-20 minutes, then adding an ethanol solution of a silane coupling agent, stirring at 80-85°C for 4-4.5 hours, vacuum filtering, washing with deionized water and ethanol three times each, and vacuum drying at 40-45°C to obtain NH2-glass flakes; in a protective gas atmosphere, reflux the reaction product 1 at 100-105°C for 1-1.2 hours, cool to 50-55°C, add methanol and NH2-glass flakes, then add sodium methoxide, and stir the reaction for 24-25 hours to obtain a reaction product 2; Furthermore, the dosage ratio of dried glass flakes, ethanol aqueous solution, and ethanol solution of silane coupling agent is 5.0-5.5g:50-55mL:700-750mL, the silane coupling agent is KH550, the dried glass flakes are obtained by drying the glass flakes at 105-110°C for 24-25h, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 4:1; the ethanol solution of silane coupling agent is obtained by adding silane coupling agent to ethanol and stirring and mixing, and the concentration is 0.1-0.15mol / L; the volume fraction of ethanol is 95%; the dosage ratio of reaction product 1, methanol, NH2-glass flakes and sodium methoxide is 25-27g:200-250mL:10-11g:0.2-0.4g; During the reaction of step A2, KH550 modifies the surface of the glass flakes to obtain NH2-glass flakes; the amino groups of the NH2-glass flakes react with the ester groups in the reaction product 1 to obtain the reaction product 2 containing fluorenone; Step A3, adding the reaction product 2, phenol and zinc chloride to concentrated hydrochloric acid, stirring and reacting at 45-50° C. for 12-13 hours, then pouring into ice water, adjusting the pH to 7.5-8, filtering, washing, recrystallizing with ethanol, and vacuum drying at 55-60° C. to obtain a bisphenol product; Further, the dosage ratio of the reaction product 2, phenol, zinc chloride, concentrated hydrochloric acid and ice water is 13-15 g: 48-50 g: 5.2-5.5 g: 330-350 mL: 3200-3300 mL; During the reaction of step A3, the fluorenone of the reaction product 2 reacts with phenol to obtain a bisphenol product containing a diazine fluorene structure and glass flakes; Step A4, in a protective gas atmosphere, heating bisphenol A, bisphenol product, epichlorohydrin, and catalyst to 75-80° C. while stirring, stirring for 3.5-4.0 hours, adding alkali solution and continuing stirring for 1-1.5 hours, extracting with toluene, washing with deionized water until neutral, separating, drying, distilling under reduced pressure, and drying at 70-75° C. to obtain a modified epoxy resin; Furthermore, the dosage ratio of bisphenol A, bisphenol product, epichlorohydrin, catalyst and alkali solution is 21-23g: 3.9-4.1g: 188-192g: 3.3-3.5g: 20-22g; the catalyst is tetrabutylammonium bromide, and the alkali solution is a sodium hydroxide solution with a mass fraction of 40-45%; During the reaction of step A4, bisphenol A, bisphenol product and epichlorohydrin react under the action of a catalyst to obtain a modified epoxy resin.

[0007] The modified polysulfide rubber is prepared by the following steps: Step B1, after mixing polysulfide rubber and 1,2-dichloroethane, add an ethanol solution of sodium hydroxide dropwise thereto, stir and react at 55-60° C. for 3-3.5 hours, and distill under reduced pressure to obtain chlorinated polysulfide rubber; in a protective gas atmosphere, add the chlorinated polysulfide rubber to a mixed solvent, stir for 10-15 minutes, then add dropwise to oleylamine, stir and react at 75-80° C. for 4.5-5 hours, add sodium hydroxide after cooling and continue stirring for 30-35 minutes, filter, and distill under reduced pressure to obtain a double bond product; Furthermore, the usage ratio of polysulfide rubber, 1,2-dichloroethane, and ethanol solution of sodium hydroxide is 1-1.5 g: 4-6 g: 200-210 mL, and the concentration of ethanol solution of sodium hydroxide is 1 g / L; the usage ratio of chlorinated polysulfide rubber, mixed solvent, oleylamine, and sodium hydroxide is 2-2.5 g: 40-50 mL: 9-11 g: 0.16-1.18 g, and the mixed solvent is isopropanol and toluene mixed in a volume ratio of 2:1; During the reaction of step B1, the polysulfide rubber and ethylene dichloride undergo a nucleophilic substitution reaction in an ethanol solution of sodium hydroxide to generate a chlorine-terminated polysulfide rubber; the chlorine-terminated polysulfide rubber and the amino group of oleylamine undergo a nucleophilic substitution reaction to obtain a polysulfide rubber containing a long alkane chain and a carbon-carbon double bond, i.e., a double bond product; Step B2, adding the double bond product to dichloromethane, stirring for 30-35 minutes, then adding m-chloroperbenzoic acid, stirring and reacting at room temperature for 8-9 hours to obtain an epoxy product; Further, the dosage ratio of the double bond product, dichloromethane, and m-chloroperbenzoic acid is 5-6 g: 75-85 mL: 19-21 g; During the reaction of step B2, the carbon-carbon double bonds in the double bond product are oxidized into epoxy groups to obtain a polysulfide rubber containing epoxy groups, i.e., an epoxy product; Step B3, stirring the epoxy product, aminopropylheptyl POSS and dimethyl sulfoxide at 50-60° C. for 24-25 hours, filtering and drying to obtain modified polysulfide rubber; Further, the usage ratio of the epoxidation product, aminopropylheptyl POSS, and dimethyl sulfoxide is 8-9 g: 18-20 g: 90-100 mL; During the reaction of step B3, the epoxy group of the epoxidation product reacts with the amino group of the aminopropylheptyl POSS to obtain a polysulfide rubber containing a hydroxyl group, POSS, etc., namely, a modified polysulfide rubber.

[0008] Beneficial effects of the invention: The invention discloses a highly weather-resistant and anti-corrosion epoxy resin coating and a preparation method thereof. The highly weather-resistant and anti-corrosion epoxy resin coating comprises raw materials such as modified epoxy resin, amino resin, urea-formaldehyde resin, and modified polysulfide rubber.

[0009] The synthesized modified epoxy resin is obtained by introducing a diazine structure and glass flakes into the epoxy resin molecular chain. The diazine structure belongs to a nitrogen-containing polycyclic heterocycle, in which the non-coordinated electrons of nitrogen and the π electrons of the benzene ring can be adsorbed on the metal surface to form a corrosion protection film; the glass flakes in the modified epoxy resin can be arranged in parallel to prevent the corrosive medium from approaching the substrate, which can not only synergistically improve the corrosion resistance of the coating with the diazine structure, but also improve the mechanical strength and heat resistance of the epoxy resin; the diazine structure has strong rigidity, which can effectively reduce the free volume of the epoxy resin cured product, hinder the movement of the polymer chain segment, increase the packing density of the polymer, and is beneficial to the improvement of the heat resistance of the coating, thereby synergistically improving the weather resistance of the coating in a high temperature environment with the glass flakes.

[0010] The synthesized modified polysulfide rubber is obtained by introducing POSS, hydroxyl groups and alkane long chains into the polysulfide rubber molecular chain. Hydroxyl groups can form a denser hydrogen bond cross-linking network between the modified polysulfide rubber and modified epoxy resin, etc., preventing water molecules in a humid environment from penetrating into the epoxy resin coating; the alkane long chain is hydrophobic and produces an intramolecular synergistic effect with the hydroxyl group, thereby improving the weather resistance of the epoxy resin coating in a high humidity environment; POSS has extremely high thermal stability and structural stability, which can not only improve the heat resistance of the modified polysulfide rubber, making it more suitable for epoxy resin coatings with higher heat resistance requirements, but also cooperate with the rigid diazine structure and glass flakes in the modified epoxy resin to improve the weather resistance of the epoxy resin coating in a high temperature environment.

[0011] In summary, the epoxy resin coating of the present invention has excellent corrosion resistance, mechanical strength, and weather resistance under high temperature and high humidity environments, and is worthy of popularization and use. DETAILED DESCRIPTION

[0012] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1

[0013] A modified epoxy resin, the preparation of which comprises the following steps: Step A1, adding 1,10-phenanthroline-2-carboxylic acid methyl ester and potassium hydroxide to deionized water and stirring at 75°C for 20 minutes, then adding potassium permanganate aqueous solution dropwise thereto, and completing the addition within 4.5 hours, continuing to stir and react for 3 hours, hot filtering, concentrating, recrystallizing in water, and vacuum drying at 70°C overnight to obtain reaction product 1; the amount ratio of 1,10-phenanthroline-2-carboxylic acid methyl ester, potassium hydroxide, deionized water, and potassium permanganate aqueous solution is 3.8g:2.6g:170mL:111mL; the potassium permanganate aqueous solution is obtained by adding 6.5g of potassium permanganate to 105mL of deionized water and stirring and mixing; Step A2, add the dried glass flakes to an ethanol-water solution and stir for 15 minutes, then add an ethanol solution of a silane coupling agent, stir at 80°C for 4 hours, vacuum filter, wash three times with deionized water and ethanol respectively, and vacuum dry at 40°C to obtain NH2-glass flakes; in a nitrogen atmosphere, reflux the reaction product 1 at 100°C and stir for 1 hour, cool to 50°C, add methanol and NH2-glass flakes, then add sodium methoxide, and stir the reaction for 24 hours to obtain a reaction product 2; the amount ratio of the dried glass flakes, the ethanol-water solution, and the ethanol solution of the silane coupling agent is 5.0 g: 50mL: 700mL, the silane coupling agent is KH550, the dried glass flakes are obtained by drying the glass flakes (supplier: Lingshou County Hengxin Mineral Products Processing Plant, 200 mesh) at 105°C for 24h, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 4: 1; the ethanol solution of the silane coupling agent is obtained by adding the silane coupling agent to ethanol and stirring and mixing, and the concentration is 0.1mol / L; the volume fraction of the ethanol is 95%; the amount ratio of the reaction product 1, methanol, NH2-glass flakes and sodium methoxide is 25g: 200mL: 10g: 0.2g; Step A3, adding the reaction product 2, phenol and zinc chloride to concentrated hydrochloric acid, stirring and reacting at 45°C for 12 hours, then pouring into ice water, adjusting the pH to 8, filtering, washing, recrystallizing from ethanol, and vacuum drying at 55°C to obtain a bisphenol product; the amount ratio of the reaction product 2, phenol, zinc chloride, concentrated hydrochloric acid and ice water is 13g:48g:5.2g:330mL:3200mL; Step A4. In a nitrogen atmosphere, bisphenol A (supplier: Shandong Baiyao Chemical Co., Ltd.), bisphenol product, epichlorohydrin, and catalyst were heated to 75°C with stirring, stirred for 3.5 hours, and then alkali solution was added and stirred for 1 hour. The mixture was extracted with toluene, washed with deionized water until neutral, separated, dried, distilled under reduced pressure, and dried at 70°C to obtain a modified epoxy resin. The dosage ratio of bisphenol A, bisphenol product, epichlorohydrin, catalyst, and alkali solution was 21g:3.9g:188g:3.3g:20g. The catalyst was tetrabutylammonium bromide, and the alkali solution was a sodium hydroxide solution with a mass fraction of 40%. Example 2

[0014] A modified epoxy resin, the preparation of which comprises the following steps: Step A1, adding 1,10-phenanthroline-2-carboxylic acid methyl ester and potassium hydroxide to deionized water, stirring at 80°C for 25 minutes, and then adding potassium permanganate aqueous solution dropwise thereto, the addition is completed within 4.7 hours, and the reaction is continued with stirring for 3.3 hours, and then hot filtration, concentration, recrystallization in water, and vacuum drying at 75°C overnight to obtain reaction product 1; the amount ratio of 1,10-phenanthroline-2-carboxylic acid methyl ester, potassium hydroxide, deionized water, and potassium permanganate aqueous solution is 3.9g:2.7g:173mL:113mL; the potassium permanganate aqueous solution is obtained by adding 6.6g of potassium permanganate to 108mL of deionized water and stirring and mixing; Step A2, adding dried glass flakes to ethanol aqueous solution and stirring for 17 minutes, then adding ethanol solution of silane coupling agent, stirring at 83°C for 4.3 hours, vacuum filtering, washing with deionized water and ethanol three times each, and vacuum drying at 43°C to obtain NH2-glass flakes; in a nitrogen atmosphere, reflux and stir the reaction product 1 at 100°C for 1.1 hours, cool to 53°C, add methanol and NH2-glass flakes, then add sodium methoxide, and stir for 24 hours to obtain reaction product 2; the amount ratio of dried glass flakes, ethanol aqueous solution, and ethanol solution of silane coupling agent is 5. 3g:53mL:730mL, the silane coupling agent is KH550, the dried glass flakes are obtained by drying the glass flakes (supplier: Lingshou County Hengxin Mineral Products Processing Plant, 200 mesh) at 105°C for 24h, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 4:1; the ethanol solution of the silane coupling agent is obtained by adding the silane coupling agent to ethanol and stirring and mixing, and the concentration is 0.1mol / L; the volume fraction of the ethanol is 95%; the amount ratio of the reaction product 1, methanol, NH2-glass flakes and sodium methoxide is 26g:230mL:10.5g:0.3g; Step A3, adding the reaction product 2, phenol and zinc chloride to concentrated hydrochloric acid, stirring and reacting at 48°C for 12.5h, pouring into ice water, adjusting the pH to 8, filtering, washing, recrystallizing from ethanol, and vacuum drying at 58°C to obtain a bisphenol product; the amount ratio of the reaction product 2, phenol, zinc chloride, concentrated hydrochloric acid and ice water is 14g:49g:5.3g:340mL:3250mL; Step A4, in a protective gas atmosphere, bisphenol A (supplier: Shandong Baiyao Chemical Co., Ltd.), bisphenol product, epichlorohydrin, and catalyst were heated to 80°C with stirring, stirred for 3.7 hours, and then alkali solution was added and stirred for 1.3 hours. The mixture was extracted with toluene, washed with deionized water until neutral, separated, dried, distilled under reduced pressure, and dried at 70°C to obtain a modified epoxy resin; the dosage ratio of bisphenol A, bisphenol product, epichlorohydrin, catalyst, and alkali solution was 22g:4.0g:190g:3.4g:21g; the catalyst was tetrabutylammonium bromide, and the alkali solution was a sodium hydroxide solution with a mass fraction of 43%. Example 3

[0015] A modified epoxy resin, the preparation of which comprises the following steps: Step A1, adding 1,10-phenanthroline-2-carboxylic acid methyl ester and potassium hydroxide to deionized water, stirring at 80° C. for 30 min, then adding potassium permanganate aqueous solution dropwise thereto, the addition is completed within 5 h, and the reaction is continued with stirring for 3.5 h, followed by hot filtration, concentration, recrystallization in water, and vacuum drying at 80° C. overnight to obtain a reaction product 1; the amount ratio of 1,10-phenanthroline-2-carboxylic acid methyl ester, potassium hydroxide, deionized water, and potassium permanganate aqueous solution is 4.0 g: 2.8 g: 175 mL: 115 mL; the potassium permanganate aqueous solution is obtained by adding 6.7 g of potassium permanganate to 110 mL of deionized water and stirring and mixing; Step A2, add the dried glass flakes to an ethanol-water solution and stir for 20 minutes, then add an ethanol solution of a silane coupling agent, stir at 85°C for 4.5 hours, vacuum filter, wash three times with deionized water and ethanol respectively, and vacuum dry at 45°C to obtain NH2-glass flakes; in a nitrogen atmosphere, reflux the reaction product 1 at 105°C and stir for 1.2 hours, cool to 55°C, add methanol and NH2-glass flakes, then add sodium methoxide, and stir the reaction for 25 hours to obtain a reaction product 2; the amount ratio of the dried glass flakes, the ethanol-water solution, and the ethanol solution of the silane coupling agent is 5 .5g:55mL:750mL, the silane coupling agent is KH550, the dried glass flakes are obtained by drying the glass flakes (supplier: Lingshou County Hengxin Mineral Products Processing Plant, 200 mesh) at 110°C for 25h, the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 4:1; the ethanol solution of the silane coupling agent is obtained by adding the silane coupling agent to ethanol and stirring and mixing, and the concentration is 0.1mol / L; the volume fraction of the ethanol is 95%; the amount ratio of the reaction product 1, methanol, NH2-glass flakes and sodium methoxide is 27g:250mL:11g:0.4g; Step A3, adding the reaction product 2, phenol and zinc chloride to concentrated hydrochloric acid, stirring and reacting at 50°C for 13 hours, then pouring into ice water, adjusting the pH to 8, filtering, washing, recrystallizing from ethanol, and vacuum drying at 60°C to obtain a bisphenol product; the amount ratio of the reaction product 2, phenol, zinc chloride, concentrated hydrochloric acid and ice water is 15g:50g:5.5g:350mL:3300mL; Step A4. In a nitrogen atmosphere, bisphenol A (supplier: Shandong Baiyao Chemical Co., Ltd.), bisphenol product, epichlorohydrin, and catalyst were heated to 80°C with stirring, stirred for 4.0 hours, and then alkali solution was added and stirred for 1.5 hours. The mixture was extracted with toluene, washed with deionized water until neutral, separated, dried, distilled under reduced pressure, and dried at 75°C to obtain a modified epoxy resin. The dosage ratio of bisphenol A, bisphenol product, epichlorohydrin, catalyst, and alkali solution was 23g:4.1g:192g:3.5g:22g. The catalyst was tetrabutylammonium bromide, and the alkali solution was a sodium hydroxide solution with a mass fraction of 45%. Example 4

[0016] A modified polysulfide rubber, the preparation of which comprises the following steps: Step B1, after polysulfide rubber (supplier: Hubei Maidehao Biotechnology Co., Ltd.) and 1,2-dichloroethane are mixed, an ethanol solution of sodium hydroxide is added dropwise thereto, the mixture is stirred at 55°C for 3 hours, and the chlorinated polysulfide rubber is obtained by distillation under reduced pressure; in a nitrogen atmosphere, the chlorinated polysulfide rubber is added to a mixed solvent and stirred for 10 minutes, then added dropwise to oleylamine, stirred at 75°C for 4.5 hours, sodium hydroxide is added after cooling and continued to be stirred for 30 minutes, and a double bond product is obtained by filtration and distillation under reduced pressure; the amount ratio of polysulfide rubber, 1,2-dichloroethane, and the ethanol solution of sodium hydroxide is 1g:4g:200mL, and the concentration of the ethanol solution of sodium hydroxide is 1g / L; the amount ratio of chlorinated polysulfide rubber, mixed solvent, oleylamine, and sodium hydroxide is 2g:40mL:9g:0.16g, and the mixed solvent is obtained by mixing isopropanol and toluene in a volume ratio of 2:1; Step B2, adding the double bond product to dichloromethane, stirring for 30 minutes, then adding m-chloroperbenzoic acid, stirring and reacting at room temperature for 8 hours to obtain an epoxy product; the dosage ratio of the double bond product, dichloromethane, and m-chloroperbenzoic acid is 5g:75mL:19g; Step B3, stirring the epoxidation product, aminopropylheptyl POSS and dimethyl sulfoxide at 50° C. for 24 hours, filtering and drying to obtain modified polysulfide rubber; the amount ratio of the epoxidation product, aminopropylheptyl POSS and dimethyl sulfoxide is 8g:18g:90mL. Example 5

[0017] A modified polysulfide rubber, the preparation of which comprises the following steps: Step B1, after polysulfide rubber (supplier: Hubei Maidehao Biotechnology Co., Ltd.) and 1,2-dichloroethane are mixed, an ethanol solution of sodium hydroxide is added dropwise thereto, the mixture is stirred at 55°C for 3.3 hours, and the chlorinated polysulfide rubber is obtained by distillation under reduced pressure; in a nitrogen atmosphere, the chlorinated polysulfide rubber is added to a mixed solvent and stirred for 13 minutes, then added dropwise to oleylamine, stirred at 75°C for 4.7 hours, sodium hydroxide is added after cooling and continued to be stirred for 33 minutes, and a double bond product is obtained by filtration and distillation under reduced pressure; the amount ratio of polysulfide rubber, 1,2-dichloroethane, and the ethanol solution of sodium hydroxide is 1.3g:5g:205mL, and the concentration of the ethanol solution of sodium hydroxide is 1g / L; the amount ratio of chlorinated polysulfide rubber, mixed solvent, oleylamine, and sodium hydroxide is 2.3g:45mL:10g:0.17g, and the mixed solvent is obtained by mixing isopropanol and toluene in a volume ratio of 2:1; Step B2, adding the double bond product to dichloromethane, stirring for 33 minutes, then adding m-chloroperbenzoic acid, stirring and reacting at room temperature for 8.5 hours to obtain an epoxy product; the dosage ratio of the double bond product, dichloromethane, and m-chloroperbenzoic acid is 5.5 g:80 mL:20 g; Step B3, stirring the epoxy product, aminopropylheptyl POSS and dimethyl sulfoxide at 55° C. for 24.5 h, filtering and drying to obtain modified polysulfide rubber; the amount ratio of the epoxy product, aminopropylheptyl POSS and dimethyl sulfoxide is 8.5 g:19 g:95 mL. Example 6

[0018] A modified polysulfide rubber, the preparation of which comprises the following steps: Step B1, after polysulfide rubber (supplier: Hubei Maidehao Biotechnology Co., Ltd.) and 1,2-dichloroethane are mixed, an ethanol solution of sodium hydroxide is added dropwise thereto, the mixture is stirred at 60°C for 3.5 hours, and the chlorinated polysulfide rubber is obtained by distillation under reduced pressure; in a protective gas atmosphere, the chlorinated polysulfide rubber is added to a mixed solvent and stirred for 15 minutes, then added dropwise to oleylamine, stirred at 80°C for 5 hours, sodium hydroxide is added after cooling, and stirring is continued for 35 minutes, and a double bond product is obtained by filtering and distillation under reduced pressure; the amount ratio of polysulfide rubber, 1,2-dichloroethane, and the ethanol solution of sodium hydroxide is 1.5g:6g:210mL, and the concentration of the ethanol solution of sodium hydroxide is 1g / L; the amount ratio of chlorinated polysulfide rubber, mixed solvent, oleylamine, and sodium hydroxide is 2.5g:50mL:11g:1.18g, and the mixed solvent is obtained by mixing isopropanol and toluene in a volume ratio of 2:1; Step B2, adding the double bond product to dichloromethane, stirring for 35 minutes, then adding m-chloroperbenzoic acid, stirring and reacting at room temperature for 9 hours to obtain an epoxy product; the dosage ratio of the double bond product, dichloromethane, and m-chloroperbenzoic acid is 6g:85mL:21g; Step B3, stirring the epoxy product, aminopropylheptyl POSS and dimethyl sulfoxide at 60° C. for 25 hours, filtering and drying to obtain modified polysulfide rubber; the amount ratio of the epoxy product, aminopropylheptyl POSS and dimethyl sulfoxide is 9g:20g:100mL. Example 7

[0019] A highly weather-resistant and anticorrosive epoxy resin coating, comprising the following raw materials in parts by weight: 50 parts of modified epoxy resin, 30 parts of amino resin, 15 parts of urea-formaldehyde resin, 10 parts of modified polysulfide rubber, 8 parts of titanium dioxide, 3 parts of kaolin, 0.5 parts of dispersant, 0.6 parts of leveling agent, 0.2 parts of defoamer, 0.8 parts of drying agent and 15 parts of solvent; the dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is potassium isooctanoate, and the solvent is ethyl acetate; The preparation of the highly weather-resistant and anti-corrosion epoxy resin coating comprises the following steps: the modified epoxy resin obtained in Example 1, the urea-formaldehyde resin (supplier: Shandong Haoyao New Materials Co., Ltd.) and the modified polysulfide rubber obtained in Example 4 are stirred and mixed at 80° C. for 2 hours, and then an amino resin (supplier: Shandong Wangtong Chemical Co., Ltd.) is added and stirred at 60° C. for 1 hour, and then titanium dioxide, kaolin, dispersant, leveling agent, defoamer, drying agent and solvent are added and stirred at 60° C. for 1.5 hours to obtain a highly weather-resistant and anti-corrosion epoxy resin coating. Example 8

[0020] A highly weather-resistant and anti-corrosion epoxy resin coating, comprising the following raw materials in parts by weight: 53 parts of modified epoxy resin, 33 parts of amino resin, 16 parts of urea-formaldehyde resin, 11 parts of modified polysulfide rubber, 9 parts of titanium dioxide, 4 parts of kaolin, 0.8 parts of dispersant, 0.7 parts of leveling agent, 0.3 parts of defoamer, 0.9 parts of drying agent and 17 parts of solvent; the dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is potassium isooctanoate, and the solvent is ethyl acetate; The preparation of the highly weather-resistant and anti-corrosion epoxy resin coating comprises the following steps: the modified epoxy resin obtained in Example 2, the urea-formaldehyde resin (supplier: Shandong Haoyao New Materials Co., Ltd.) and the modified polysulfide rubber obtained in Example 5 are stirred and mixed at 85°C for 2.3 hours, and then the amino resin (supplier: Shandong Wangtong Chemical Co., Ltd.) is added and stirred at 65°C for 1.3 hours, and then titanium dioxide, kaolin, dispersant, leveling agent, defoamer, drying agent and solvent are added and stirred at 65°C for 1.7 hours to obtain the highly weather-resistant and anti-corrosion epoxy resin coating. Example 9

[0021] A highly weather-resistant and anti-corrosion epoxy resin coating, comprising the following raw materials in parts by weight: 55 parts of modified epoxy resin, 35 parts of amino resin, 17 parts of urea-formaldehyde resin, 12 parts of modified polysulfide rubber, 10 parts of titanium dioxide, 5 parts of kaolin, 1.0 part of dispersant, 0.8 part of leveling agent, 0.4 part of defoamer, 1.0 part of drying agent and 20 parts of solvent; the dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is potassium isooctanoate, and the solvent is ethyl acetate; The preparation of the highly weather-resistant and anti-corrosion epoxy resin coating comprises the following steps: the modified epoxy resin obtained in Example 3, the urea-formaldehyde resin (supplier: Shandong Haoyao New Materials Co., Ltd.) and the modified polysulfide rubber obtained in Example 6 are stirred and mixed at 90° C. for 2.5 hours, and then an amino resin (supplier: Shandong Wangtong Chemical Co., Ltd.) is added and stirred at 70° C. for 1.5 hours, and then titanium dioxide, kaolin, dispersant, leveling agent, defoamer, drying agent and solvent are added and stirred at 70° C. for 2.0 hours to obtain a highly weather-resistant and anti-corrosion epoxy resin coating.

[0022] Comparative Example 1 Compared with Example 9, the NH2-glass flakes in the preparation process of the modified epoxy resin are replaced with 1-aminopentane, and the rest is exactly the same as Example 9 to prepare the epoxy resin coating.

[0023] Comparative Example 2 Compared with Example 9, the reaction product 1 in the preparation process of the modified epoxy resin was replaced with 9-fluorenone-2,7-dicarboxylic acid methyl ester, and the rest was exactly the same as Example 9 to prepare an epoxy resin coating.

[0024] Comparative Example 3 Compared with Example 9, the bisphenol product in the preparation process of the modified epoxy resin was replaced with methyl 2,2-bis(4-hydroxyphenyl)acetate, and the rest was exactly the same as Example 9 to prepare an epoxy resin coating.

[0025] Comparative Example 4 Compared with Example 9, the oleylamine in the preparation process of the modified polysulfide rubber was replaced with N-methylallylamine, and the rest was exactly the same as Example 9 to prepare the epoxy resin coating.

[0026] Comparative Example 5 Compared with Example 9, the modified polysulfide rubber used was replaced with a double-bond product, and the rest was exactly the same as Example 9 to prepare an epoxy resin coating.

[0027] The epoxy resin coating prepared by the present invention is further tested for its effect, and the test results are as follows.

[0028] Corrosion inhibition efficiency: The epoxy resin coating was scraped onto the surface of a standard test steel plate cleaned and dried with anhydrous ethanol to obtain a test sample. The coating dry film thickness was (50±5) μm. After curing at 60°C for 3 days, an electrochemical impedance test was performed. Electrochemical impedance test: A three-electrode system was used, with the working electrode being the coating / standard test steel plate, the reference electrode being a saturated calomel electrode, and the counter electrode being a graphite electrode. The test sample was immersed in a 3.5% NaCl solution for 7 days before testing. The test frequency range was 10 5 -10 -2 Hz, the amplitude of the test sine wave signal is 50mV, the test is carried out at open circuit potential and room temperature, and the instrument used is CS310H electrochemical workstation; the surface charge transfer resistance R1 (of the sample to be tested) and R0 (of the standard steel plate without coating protection) are recorded, and the corrosion inhibition efficiency is calculated, the corrosion inhibition efficiency = (R1-R0) / R1×100%, and the results are recorded in Table 1; Tensile strength: According to the method specified in GB / T 528-2009, the tensile strength was tested using a universal tensile testing machine, and the moving speed of the clamp was set to 10 mm / min. The results are recorded in Table 1; Weather resistance (high temperature environment): Place the test sample in a 160°C oven for 12 hours, measure and calculate the tensile strength retention rate according to the above method, and record the results in Table 1; Weather resistance (high humidity environment): Soak the test sample in water for 12 hours, measure and calculate the tensile strength retention rate according to the above method, and record the results in Table 1; Table 1: Test results Example 7 Example 8 Example 9 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Corrosion inhibition efficiency (%) 92.85 93.02 93.18 86.62 85.28 85.42 93.15 93.16 Tensile strength (MPa) 15.3 15.5 16.1 12.7 15.9 15.6 15.9 15.6 Tensile strength retention after high temperature treatment (%) 96.2 96.4 96.9 92.7 96.8 92.6 96.8 92.4 Tensile strength retention after high humidity treatment (%) 95.6 95.8 96.1 96.0 96.1 96.0 91.1 91.5 According to the data in Table 1, the epoxy resin coating of the present invention has excellent corrosion resistance, mechanical strength and weather resistance in high temperature and high humidity environments. Comparison of Example 9 with Comparative Example 1 shows that the NH2-glass flakes in the preparation process of the modified epoxy resin are replaced with 1-aminopentane, and glass flakes are not introduced into the epoxy resin molecular chain. It can neither cooperate with the diazine fluorene structure to improve the corrosion resistance of the coating, nor improve the mechanical strength and heat resistance of the epoxy resin, resulting in a decrease in the corrosion inhibition efficiency, tensile strength and tensile strength retention rate of the coating in a high temperature environment. Comparison of Example 9 with Comparative Example 2 shows that the reaction product 1 in the preparation process of the modified epoxy resin is replaced with 9-fluorenone-2,7-dicarboxylic acid methyl ester, and a nitrogen-free rigid fluorene structure is introduced into the epoxy resin molecular chain. A corrosion protection film cannot be formed, and thus the corrosion resistance of the coating cannot be coordinated with the glass flakes, resulting in a decrease in the corrosion inhibition efficiency of the coating. Comparison of Example 9 with Comparative Example 3 shows that the bisphenol product in the preparation process of the modified epoxy resin is replaced with methyl 2,2-bis(4-hydroxyphenyl)acetate, and the diazine structure is not introduced into the epoxy resin molecular chain, which can neither cooperate with the glass flakes to improve the corrosion resistance of the coating, nor cooperate with the glass flakes and POSS to improve the weather resistance of the coating in a high temperature environment, resulting in a decrease in the corrosion inhibition efficiency of the coating and the tensile strength retention rate in a high temperature environment. Comparison of Example 9 with Comparative Example 4 shows that the oleylamine in the preparation process of the modified polysulfide rubber is replaced with N-methylallylamine, and no alkane long chain is introduced, and intramolecular synergy with the hydroxyl group cannot be produced, so that the weather resistance of the epoxy resin coating in a high humidity environment decreases, resulting in a decrease in the tensile strength retention rate of the coating in a high humidity environment. Comparison of Example 9 with Comparative Example 5 shows that replacing the modified polysulfide rubber with a double bond product without introducing POSS and hydroxyl groups can neither synergize with the diazine structure and glass flakes to improve the weather resistance of the coating in a high temperature environment, nor produce an intramolecular synergistic effect with the long chain of alkane, which reduces the weather resistance of the epoxy resin coating in a high humidity environment and causes a decrease in the tensile strength retention rate of the coating in a high temperature and high humidity environment.

[0029] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.

Claims

1. A highly weather-resistant and anti-corrosion epoxy resin coating, characterized in that: The invention comprises the following raw materials in parts by weight: 50-55 parts of modified epoxy resin, 30-35 parts of amino resin, 15-17 parts of urea-formaldehyde resin, 10-12 parts of modified polysulfide rubber, 8-10 parts of titanium dioxide, 3-5 parts of kaolin, 0.5-1.0 parts of dispersant, 0.6-0.8 parts of leveling agent, 0.2-0.4 parts of defoamer, 0.8-1.0 parts of drying agent and 15-20 parts of solvent; The modified epoxy resin is prepared by the following steps: Step A1, adding 1,10-phenanthroline-2-carboxylic acid methyl ester and potassium hydroxide to deionized water, and then dropping potassium permanganate aqueous solution therein, and continuing to stir the reaction after the dropwise addition to obtain a reaction product 1; Step A2, adding the dried glass flakes into an ethanol aqueous solution, and then adding an ethanol solution of a silane coupling agent, stirring and reacting to obtain NH2-glass flakes; In a protective gas atmosphere, the reaction product 1 was refluxed and stirred, then cooled and methanol and NH2-glass flakes were added, and then sodium methoxide was added, and the reaction was stirred to obtain the reaction product 2; Step A3, adding the reaction product 2, phenol and zinc chloride to concentrated hydrochloric acid, stirring for reaction, pouring into ice water, adjusting the pH and post-treating to obtain a bisphenol product; Step A4: In a protective gas atmosphere, bisphenol A, bisphenol product, epichlorohydrin, a catalyst, and an alkali solution are mixed and stirred to react to obtain a modified epoxy resin.

2. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: The dispersant is BYK-2070, the leveling agent is BYK-306, the defoamer is BYK-A530, the drying agent is potassium isooctanoate, and the solvent is ethyl acetate.

3. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: In step A1, the usage ratio of 1,10-phenanthroline-2-carboxylic acid methyl ester, potassium hydroxide, deionized water, and potassium permanganate aqueous solution is 3.8-4.0 g: 2.6-2.8 g: 170-175 mL: 111-115 mL; the potassium permanganate aqueous solution is obtained by adding 6.5-6.7 g of potassium permanganate to 105-110 mL of deionized water and stirring and mixing.

4. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: In step A2, the dosage ratio of dried glass flakes, ethanol aqueous solution, and ethanol solution of silane coupling agent is 5.0-5.5g:50-55mL:700-750mL, the silane coupling agent is KH550, the dried glass flakes are obtained by drying the glass flakes at 105-110°C for 24-25h, and the volume ratio of ethanol to deionized water in the ethanol aqueous solution is 4:

1.

5. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: In step A2, the ethanol solution of the silane coupling agent is obtained by adding the silane coupling agent to ethanol and stirring and mixing, and the concentration is 0.1-0.15 mol / L; the volume fraction of the ethanol is 95%; the amount ratio of the reaction product 1, methanol, NH2-glass flakes and sodium methoxide is 25-27g:200-250mL:10-11g:0.2-0.4g.

6. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: In step A3, the dosage ratio of reaction product 2, phenol, zinc chloride, concentrated hydrochloric acid and ice water is 13-15g: 48-50g: 5.2-5.5g: 330-350mL: 3200-3300mL; in step A4, the dosage ratio of bisphenol A, bisphenol product, epichlorohydrin, catalyst and alkali solution is 21-23g: 3.9-4.1g: 188-192g: 3.3-3.5g: 20-22g; the catalyst is tetrabutylammonium bromide, and the alkali solution is a sodium hydroxide solution with a mass fraction of 40-45%.

7. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: The modified polysulfide rubber is prepared by the following steps: Step B1, after mixing polysulfide rubber and 1,2-dichloroethane, add an ethanol solution of sodium hydroxide dropwise thereto, stir and react at 55-60° C. for 3-3.5 hours, and distill under reduced pressure to obtain chlorinated polysulfide rubber; in a protective gas atmosphere, add the chlorinated polysulfide rubber to a mixed solvent, stir for 10-15 minutes, then add dropwise to oleylamine, stir and react at 75-80° C. for 4.5-5 hours, add sodium hydroxide after cooling and continue stirring for 30-35 minutes, filter, and distill under reduced pressure to obtain a double bond product; Step B2, adding the double bond product to dichloromethane, stirring for 30-35 minutes, then adding m-chloroperbenzoic acid, stirring and reacting at room temperature for 8-9 hours to obtain an epoxy product; Step B3, stirring the epoxy product, aminopropylheptyl POSS and dimethyl sulfoxide at 50-60° C. for 24-25 hours, filtering and drying to obtain the modified polysulfide rubber.

8. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: In step B1, the usage ratio of polysulfide rubber, 1,2-dichloroethane, and ethanol solution of sodium hydroxide is 1-1.5 g: 4-6 g: 200-210 mL, and the concentration of ethanol solution of sodium hydroxide is 1 g / L; the usage ratio of chlorinated polysulfide rubber, mixed solvent, oleylamine, and sodium hydroxide is 2-2.5 g: 40-50 mL: 9-11 g: 0.16-1.18 g, and the mixed solvent is isopropanol and toluene mixed in a volume ratio of 2:

1.

9. The highly weather-resistant and anticorrosive epoxy resin coating according to claim 1, characterized in that: In step B2, the ratio of double bond product, dichloromethane and m-chloroperbenzoic acid is 5-6 g:75-85 mL:19-21 g; In step B3, the usage ratio of the epoxidation product, aminopropylheptyl POSS and dimethyl sulfoxide is 8-9 g: 18-20 g: 90-100 mL.

10. A method for preparing the highly weather-resistant and anticorrosive epoxy resin coating according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: stirring and mixing modified epoxy resin, urea-formaldehyde resin and modified polysulfide rubber at 80-90°C for 2-2.5h, adding amino resin and stirring at 60-70°C for 1-1.5h, adding titanium dioxide, kaolin, dispersant, leveling agent, defoamer, drying agent and solvent and continuing stirring at 60-70°C for 1.5-2.0h to obtain a highly weather-resistant and anti-corrosion epoxy resin coating.

Citation Information

Patent Citations

  • High temperature-resistant and wear-resistant heavy-duty anticorrosive paint and preparation method thereof

    CN102898926A

  • Glass flake modified polyurea coating

    CN105038544A

  • Epoxy resin curing agent, and preparation method and application of epoxy resin curing agent

    CN108084436A

  • High-temperature-resistant high-pressure graphene modified primer-topcoat anticorrosive coating

    CN109486364A

  • Nano-modified epoxy resin anticorrosive paint and preparation method thereof

    CN110669408A

Cited By

  • Rubber adhesive for improving wear resistance by applying wet-skid-resistant epoxy resin and preparation process of rubber adhesive

    CN120310493A